Analysis of Domestic Violence Using an Ecofeminist Perspective - Putri, Rizca Yunike; Soleh, Mochamad Fajar; Suharnanik, Suharnanik (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
The problem of domestic violence (KDRT) is not something new to Indonesia. Domestic violence cases that occur in Indonesia generally always involve women as victims of violence. This occurs due to the unequal power relations between men and women in the household. This research uses a qualitative approach through the literature study method, attempting to analyze the phenomenon of domestic violence using an eco-femenism perspective. In an ecofeminist perspective, women and nature have a correlational relationship. Women and nature both experience oppression carried out by a patriarchal society. Ecofeminism is a theory that connects environmental issues and gender issues. In the context of domestic violence, ecofeminism can be used to analyze and understand the impact of such violence on the natural environment, as well as how environmental issues can interact with gender issues in this context. Ecofeminism can provide an in-depth look at how domestic violence and environmental issues are interrelated and can help in designing more holistic solutions to both issues. Based on research results, cases of domestic violence can be minimized if couples apply ecofeminist principles in their married life. The principles of ecofeminism include: responsibility towards nature, cosmic solidarity, harmony with nature, equal relations and caring.